Oldsagssamlinger på danske herregårde - Poulsen, Karen Løkkegaard (Kuml, 2001)
Collections of antiquities on Danish manors Before the establishment of the public museum system and during its first phase after 1807, important activity concerning the relics of antiquity was managed by the estates (fig. 3). This resulted in the creation of collections with varied contents, including Danish antiquities. These were either bought or found within the estate district as was the case with the pieces of ”danefæ”, which the peasants found and brought to the manor (according to a decree from 1737, all treasures found in the Danish soil must be handed over to the king or – later – the state. Such finds are called” danefæ”). It is notable that the collection of danefæ took place according to a decentralised structure, as described in King Frederik V’s public notice from 1752, which also stated that a reward is given in return. According to this, the king delegated his right to collect danefæ to counts and barons, who could then again pass it on and cash the reward. The danefæ became the nucleus in many collections (fig. 4). This category of landowners kept their central position to archaeological work for a long time. Their right to collect danefæ lasted until 1853, and the practice of delivering antiquities found on the estate at the manor went on until modern times. The early museum collections, the kunstkammers and collections of curios of the 17th and 18th centuries, are well described in the literature on museum history. However, only little attention has been paid to the collections of the 19th and early 20th centuries. For instance, the collections of Broholm on Fyn (fig. 9), of Nr. Vosbjerg in Western Jutland, of Brattingsborg on Samsø, and of Valbygaard (fig. 1) and Lerchenborg on Sjælland have all been thoroughly described, but only individually (note 5), not as a phenomenon. This article is based on information from a few selected archives supplemented by spot tests involving a number of manors and several museums in areas with many estates (note 14). ln spite of the limitations induced by the source material it is the aim of the article to throw light on as many collections as possible to reach a general view. The article focuses on the manor collections as a phenomenon and on the museum development and museum traditions to which these collections belong , with the emphasis on the 19th and early 20th centuries. The article is based on two archives,Victor Hermansen’s papers in the Royal Library, indicated in the lists I-V with the signature of ”gl. Bib. VH” and the part of the report archive in the National Museum / Danish Prehistory, listed as ”NM, Oldtiden”, which contains the private collections. The material has been described using five time references: Before 1807 (list I); 1807-1848 (list II); 1848-1892 (list III); and finally 1892-1919 and 1919- the present time (both in list IV) (fig. 2). The time divisions were the result of an overall evaluation of the material, the type of collections and the intellectual, mental and social motives behind the collecting activity. Although the types of collections from different periods overlap and late examples of early collection types do occur, it is still obvious that the ideal for collector’s activity changed in the course of time. The review begins with the period 1807-1848, at the start of which the ”Royal Commission to the Safe keeping of Antiquities” was to become the foundation stone of the public museum system. 1807-1848: landowners and others put much work into the issue, which the ”Commission” had been appointed to safeguarding. Danish artefacts were collected as never before. A flow of artefacts arrived at the collection in the capital from several landowners on Fyn and elsewhere. As in the beginning of the previous period, the landowners were also taking part in excavations, in protecting relics of antiquity and in publishing archaeological treatises. 1848-1892:The public museum services were established. The new keeper of the Danish antiquities, the archaeologist J.J.A. Worsaae travelled the country to collect information, and he specifically contacted the landowners, knowing that these were key figures within archaeological research (fig. 5 and 10). Consequently, the landowners changed the way they dealt with archaeology in line with the development of the profession as initiated by Worsaae, who went in the direction of a more scholarly method and a dissociation of philosophy and history, which had been closely connected to archaeology. King Frederik VII’s (1848-1863) personal interest in archaeology had a positive influence on the development of the profession and contributed to its growing popularity among the landowners and the public. 1892-1919: This period began with the Old Nordic Museum changing its name into the National Museum, and Sophus Müller becoming its curator. The landowners continued their archaeological activity, especially on those estates, which had a tradition for this (fig. 6). However, in the correlation between these archaeologically interested and active landowners, the National Museum gained more authority due to its growing expertise. Not only did the museum engage itself in the landowners’ investigations, it also took over the work and continued it on its own terms. But at the same time the museum staff showed appropriate consideration to the landowners, who according to the constitution had the right of owners hip to extensive areas with artefacts and relics of the past. Cooperation was necessary for the growth of the profession. The landowners had unlimited rights to those finds of artefacts and structures that were not danefæ or listed relics. However, the registers of the National Museum from this time show that after the excavation, the landowner often gave the finds to the museum. This period also saw conflicts between the provincial museums and the National Museum, caused by Sophus Müller’s policy of a centralised museum structure, which gave the provincial museums little liberty of action (note 7). We lack a coherent description of the private artefact collectors’ part in this game. A closer examination of some of them, such as Beck on Valbygaard, the private collectors associated with the museum in Odense, and Collet on Lundbygaard suggests that they were sometimes on one, sometimes on the other front in this controversy (note 9 and 47). After 1919: In 1919, the privileges and special duties of the nobility were cancelled, a development parallelled in the rest of Central, East and Northern Europe. The advanced position in the government previously held by this social class had ended to be replaced by the public sector of the democratic society of which the modern museum system forms a part. However, some estates carried on the tradition of building up collections of artefacts even in this period, and a few landowners opened museums on their estates (fig. 7). These are late activities in the long tradition of archaeological activity on the manors. Both in this periods and the previous one, the interest in collecting artefacts spread down the hierarchy of the manors to the employees and to the farmers on the small holdings. Today almost every family holding owns a collection of artefacts found on the property. To throw light on the changing intellectual context of which the artefact collections on the manors formed part, from the collections of the late Renaissance until the present, the article includes the collections of curios and minerals from the 17th and 18th centuries (list I). Most royal and princely courts in Europe had a kunstkammer with a wideranging content. The archive information used for this article has shown that in Denmark in the 19th century, these collections were not exclusively connected to the nobility or the manors. It is a common trait that the collector was a learned person, an academic or a high official or a well- educated nobleman with or without property. To agree with this, both in Denmark and internationally, a well-equipped library was attached to the collection as a fixed element (fig. 8). Some kunstkammers were attached to grammar schools, orphanages and student hostels. Through purchase and sale parts of the collections changed owner and location from time to time, as for instance the collection of Jesper Friis, which can be followed in written so urces from the 17th century through the following centuries and for a couple of items even into the antique collection of the National Museum. Around 1800, the Romantic Movement and the national currents increased the interest in Danish arte facts and relics of the past. Via folk high school education, which was inspired by the Nordic mythology and attached importance to the prehistory and early history of the nation, this interest spread into the population. As opposed to the earlier collections, which formed part of a learned environment characterised by a classical, humanistic education, the many manor collections, which had their prime in the period of c. 1860-1919, formed part of a practical agronomy universe, where demanding farming techniques were pushed into effect and where hunting and outdoor life was an important part of life. At the same time the landowners put much strength into renovating buildings and erecting fine manor complexes, a natural consequence of the wealth that originated from the corn sales. In an era where natural sciences and practical trades were given pride of place, the turn of archaeology away from the old humanistic method and tradition within philology and history towards the exact sciences will have contributed to the populariry of the profession. The private collections of artefacts have a larger professional and intellectual value than what is usually attributed to them. They were made at a time when the creation of rype collections of artefacts, suites, were in fashion. Information on find conditions and contexts are therefore rare. In the 20th century, professional archaeologists valued these collections according to the presence of find information, and so many of them were split through exchange. The fact that many of these artefacts were from the time before the parish accounts (a registering of relics of the past initiated by the National Museum) and thus – when it comes to the local artefacts – told of the relics of the past that had been situated on the estate earlier, but had been demolished in the early, active farming years of the first half of the 19th century. Also, the ethnological value of these collections has been disregarded. The article ends with considerations as to the public / the private. Nowadays these two notions create two separate rooms. ICOM’s ethical rules for museums have a clear definition, stating that a professional museum activiry is in compatible with private collecting activity. The history of the private collections of arte facts throws light on the development from the time before the public sector, when landowners and other private persons were supporting archaeology and the public museum initiative economically, politically and professionally. The profession developed from here and in a continued interaction between the professionals and the private collectors. Even when today there is a clear distinction between public and private, there are some interesting reminiscences left. Without the contribution and support of the public, archaeology would have difficult conditions. Karen Løkkegaard Poulsen Maribo Translated by Annette Lerche Trolle